The relationship between methamphetamine use and heterosexual behaviour: Evidence from a prospective longitudinal study - McKetin, Rebecca; Lubman, D.; Baker, A.; Dawe, S.; Ross, J.; Mattick, R.; Degenhardt, L. (Wiley-Blackwell Publishing Ltd., 2018)
Aims: To estimate the extent to which specific sexual behaviours (being sexually active, having multiple sex partners, casual sex, condomless casual sex, anal sex and condomless anal sex) change during periods of methamphetamine use. Design: Within-person estimates for the relationship between methamphetamine use and sexual behaviour were derived from longitudinal panel data from the Methamphetamine Treatment Evaluation Study (MATES) cohort (2006-10). Setting: Sydney and Brisbane, Australia. Participants: Participants (n = 319) were recruited through treatment and other health services, self-identified as heterosexual, were aged 17-51 years, 74% were male and all were dependent on methamphetamine on study entry. Measurements: Days of methamphetamine use in the past month and sexual behaviour in the past month were both assessed using the Opiate Treatment Index. Findings: When using methamphetamine, participants had double the odds of being sexually active compared with when they were not using, after adjustment for demographics and other substance use [adjusted odds ratio (aOR) = 1.9, P = 0.010]. When participants were sexually active, they were more likely to have multiple sex partners (aOR = 3.3, P = 0.001), casual sex partners (aOR = 3.9, P < 0.001) and condomless casual sex (aOR = 2.6, P = 0.012) when using methamphetamine than when they were not using. During months when participants had a casual sex partner, there was no significant reduction in their likelihood of condom use when they were using methamphetamine. There was no significant change in the likelihood of having anal sex or condomless anal sex during months of methamphetamine use. Conclusions: Methamphetamine use is associated with an increase in being sexually active, having multiple sex partners and casual sex partners and having condomless sex with casual partners, but it is not associated with a change in condom use per se.